KAJIAN PERBANDINGAN INDEKS SOSIAL EKONOMI MASYARAKAT LINGKAR DAN NON LINGKAR USAHA PERTAMBANGAN NIKEL - Irfan Ido (Universitas Halu Oleo, 2020)
Mineral mining business, one of which is given to private business entities, must realize the mandate of the 1945 Constitution and the Minerba Law No. 04 of 2009 concerning the realization of people's prosperity, especially for people around the mining. The prosperity of the people is related to the social and economic welfare of the people. This paper aims to examine the socio-economic comparison of a circle and non-circle communities in the nickel mining business in terms of employment opportunities, income, education and public health. This research was conducted in the Matabura Village (circle mining) and Amandete Village (non-circle mining) PT. ST Nickel Resources in Amonggedo District, Konawe Regency, Southeast Sulawesi Province. The data analysis method used is quantitative descriptive using two data analysis tools, namely: percentage analysis and social-economic index analysis of the community. The conclusion of this paper is that the social-economic index of the circular community is higher than the non-circular nickel mining community, but the socio-economic index of the community is equally included in the bad category.